Alat Pemutus kWh Meter 1 Phasa Pelanggan Yang Terlambat Pembayaran Dengan Fitur Android - Arvioneta, Rizqa (INOVTEK - Seri Elektro, 2022)
Electrical energy is a source of energy that is needed by people in everyday life, especially at this time. Almost all the equipment used uses electricity so that electrical energy turns into the main needs of the community. As a user of electrical energy provided by PLN, there is an obligation that must be made, namely payment. Payments for 1-phase low-voltage customers are made every 1st to 20th of every month. In general, this power cut is carried out directly by officers in the field. During the implementation, there were several obstacles that caused the electricity to not be cut off, one of which was a locked gate. In this final project, an electric circuit breaker is designed that can be controlled remotely using an officer's smartphone. This breaker uses a relay as an electric current breaker on the customer side and is equipped with a buzzer that will light up for a few seconds and an LCD that is able to notify that the electricity is out and remind you to pay the electricity bill immediately. It is hoped that this tool will be able to reduce the number of arrears in paying customers' electricity bills to PLN.